Process cartridge and electrophotographic apparatus
The process cartridge for electrophotographic devices addresses the challenges of maintaining high image quality and effective cleaning by using a polycarbonate resin and silicon atom-containing compounds in the toner, resulting in improved long-term performance and reduced wear.
Patent Information
- Application Number
- JP2022188612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2042-11-25
AI Technical Summary
Existing electrophotographic devices face challenges in achieving high image quality and effective cleaning performance over long-term use, particularly due to issues with toner flowability and the maintenance of a blocking layer during the cleaning process.
The process cartridge incorporates an electrophotographic photoreceptor with a surface layer containing a polycarbonate resin with specific structural units, and toner particles with external additives comprising silicon atom-containing compounds, such as silica particles, to enhance image quality and cleaning performance.
This configuration improves toner flowability and reduces toner circulation before the blocking layer, leading to enhanced image quality and effective cleaning performance over long-term use, while minimizing wear on the photoreceptor.
Smart Images

Figure 0007657764000039 
Figure 0007657764000001 
Figure 0007657764000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a process cartridge and an electrophotographic apparatus having the process cartridge. [Background technology]
[0002] The electrophotographic photoreceptor used in the electrophotographic device is generally drum-shaped. The drum-shaped electrophotographic photoreceptor (hereinafter also referred to as electrophotographic photoreceptor drum) is generally used in an electrophotographic image forming process including a charging step, an exposure step, a developing step, a transfer step, and a cleaning step. In the electrophotographic image forming process, the cleaning process for removing the remaining toner on the electrophotographic photosensitive drum after the transfer process is an important process for obtaining a clear image. In this cleaning process, the method for removing the remaining toner is generally a method of pressing a rubber-like cleaning blade against the electrophotographic photosensitive drum and scraping off the toner. In recent years, in order to suppress wear of the electrophotographic photosensitive drum, a method of pressing the cleaning blade at a low contact pressure is generally used.
[0003] In recent electrophotographic apparatuses, there is a demand for further reduction in torque (reduction in the contact pressure of the cleaning blade) and for no cleaning failure to occur. In the cleaning process, a layer of small particles called a blocking layer, which is made of additives contained in the toner, is formed at the portion where the cleaning blade contacts the surface of the electrophotographic photosensitive drum. In the cleaning process, it is important to maintain this blocking layer.
[0004] A cleaning failure occurs when this blocking layer is destroyed for some reason, causing toner and external additives to slip through the cleaning blade. When a cleaning failure occurs, a streak-like image defect occurs in the image, and even if no abnormality occurs in the image, minute particles of toner and external additives that have slipped through remain on the surface of the electrophotographic photosensitive drum. As a result, minute particles of toner and external additives may adhere to the charging roller during the charging process, causing problems such as charging failure. By increasing the contact pressure of the cleaning blade, it is possible to prevent the toner from slipping through, but this causes severe wear on the electrophotographic photosensitive drum, making it impossible to use the drum for a long period of time. In addition, in order to obtain high image quality through long-term use, it is necessary to maintain high toner fluidity. By using silica particles as an external additive, the fluidity of the toner can be increased, and fog images do not occur during long-term use, allowing high image quality to be maintained. However, when the fluidity of the toner is improved, the toner circulates in front of the blocking layer of the cleaning blade, which can cause cleaning defects.
[0005] Patent Document 1 discloses an image forming apparatus using an image carrier (electrophotographic photoreceptor) having a surface layer containing a polycarbonate resin and a toner containing a fatty acid metal salt as an external additive. Patent Document 1 states that by using an image forming apparatus having the above configuration, the surface of the image carrier can be smoothly worn and uneven scraping can be suppressed, and as a result, cleaning defects can be suppressed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-83448 A Summary of the Invention [Problem to be solved by the invention]
[0007] The technology described in Patent Document 1 is effective in suppressing cleaning defects when the contact pressure of a conventional cleaning blade is used, but there is room for improvement in cleaning performance when the contact pressure of the cleaning blade is lowered to achieve low torque. Therefore, an object of the present disclosure is to provide a process cartridge that can achieve both high image quality and high cleaning performance over long-term use, and an electrophotographic apparatus having the process cartridge. [Means for solving the problem]
[0008] The above object is achieved by the present disclosure as follows. That is, the process cartridge according to one aspect of the present disclosure is A process cartridge which integrally supports an electrophotographic photosensitive member having a surface layer, a developing unit which develops an electrostatic latent image formed on the surface of the electrophotographic photosensitive member with toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning unit which cleans the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after the toner image has been transferred to a transfer material, and is detachably mountable to a main body of an electrophotographic apparatus, the surface layer of the electrophotographic photoreceptor contains a polycarbonate resin having a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structural unit represented by the following formula (3), the toner has toner particles containing a resin and an external additive, the external additive comprises particles of a silicon atom-containing compound, a content ratio of the silicon atom-containing compound particles in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to the total mass of the toner; It is characterized by: [ka] [ka] [ka] An electrophotographic apparatus according to another aspect of the present disclosure includes the above-mentioned process cartridge. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a process cartridge capable of achieving both high image quality and high cleanability even with long-term use, and an electrophotographic apparatus having the process cartridge. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic diagram illustrating an example of a schematic configuration of a process cartridge and an electrophotographic apparatus according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present disclosure will be described in detail below with reference to preferred embodiments. As a result of extensive investigation, the present inventors have found that the above-mentioned problems can be solved by configuring the process cartridge as follows.
[0012] Specifically, the process cartridge according to the present disclosure integrally supports an electrophotographic photoreceptor having a surface layer, a developing means, and a cleaning means, and is detachably mountable to the main body of an electrophotographic device. The developing means develops an electrostatic latent image formed on the surface of the electrophotographic photoreceptor with toner to form a toner image on the surface of the electrophotographic photoreceptor. The cleaning means cleans the toner remaining on the surface of the electrophotographic photoreceptor with a cleaning blade after the toner image is transferred to a transfer material. The surface layer of the electrophotographic photoreceptor contains a polycarbonate resin having a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structural unit represented by the following formula (3). [ka] [ka] [ka]
[0013] The toner has toner particles containing a resin and an external additive. Furthermore, the external additive contains particles of a silicon atom-containing compound, and the content of the particles of the silicon atom-containing compound in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to the total mass of the toner.
[0014] The present inventors believe that the mechanism by which the process cartridge having the above configuration is effective in achieving both high image quality and high cleaning performance over long-term use is as follows. By using the toner having silicon atom-containing compound particles as an external additive, it is possible to stably maintain high image quality during long-term use.However, since the external additive has high fluidity, the toner moves in a circulating manner in front of the deposition layer formed at the contact portion between the cleaning blade and the surface of the electrophotographic photoreceptor, and minute toner and external additive may leak out from the gap of the cleaning blade.As a result, streaky image defects may occur.
[0015] As a result of the inventors' investigations, it has become clear that when the surface layer of an electrophotographic photoreceptor contains a polycarbonate resin having the above-mentioned structural unit, the circulating force of the toner in front of the deposition layer is reduced, and the cleaning performance is improved. The inventors speculate as follows about the reason for this improvement in cleaning performance. Generally, the surface layer containing polycarbonate resin is worn away by cleaning. The surface layer scraped off by the wear also becomes powder (hereinafter, scraped powder) and is eventually collected by the cleaning blade, but it mixes with the toner and external additives just before the part where the cleaning blade and the electrophotographic photoreceptor contact each other. In this disclosure, it is presumed that the three-dimensional action of the polycarbonate resin having the above structural unit enhances the interaction between the toner surface and the external additives by the scraped powder, and the toner clumps, reducing the fluidity and suppressing the toner from slipping through. As shown by the above mechanism, the respective components of the electrophotographic photosensitive member and the toner in a process cartridge according to one embodiment of the present disclosure exert a synergistic effect on each other, making it possible to achieve the effects according to the present disclosure.
[0016] Hereinafter, the configuration of the electrophotographic photosensitive member of the process cartridge according to one aspect of the present disclosure will be described in detail. [Electrophotographic photoreceptor] The electrophotographic photoreceptor of the present disclosure has a surface layer. The method for manufacturing the electrophotographic photoreceptor of the present disclosure includes a method of preparing the coating liquid for each layer described later, coating the layers in the desired order, and drying the liquid. In this case, the coating liquid can be applied by dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, etc. Among these, dip coating is preferred from the viewpoint of efficiency and productivity. The support and each layer will be described below.
[0017] <Support> In the present disclosure, the electrophotographic photoreceptor has a support. In the present disclosure, the support is preferably a conductive support having electrical conductivity. In addition, the shape of the support may be a cylindrical shape, a belt shape, a sheet shape, or the like. Among them, a cylindrical support is preferable. In addition, the surface of the support may be subjected to electrochemical treatment such as anodization, blasting treatment, cutting treatment, or the like. The support is preferably made of a metal, a resin, or a glass. Examples of the metal include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. Among them, an aluminum support using aluminum is preferable. Furthermore, the resin or glass may be made conductive by a process such as mixing with or coating with a conductive material.
[0018] <Conductive layer> In the present disclosure, a conductive layer may be provided on the support. By providing the conductive layer, scratches and irregularities on the surface of the support can be concealed and light reflection on the surface of the support can be controlled. The conductive layer preferably contains conductive particles and a resin. The conductive particles may be made of a material such as metal oxide, metal, or carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, bismuth oxide, etc. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, etc. Among these, it is preferable to use metal oxides as the conductive particles, and it is particularly preferable to use titanium oxide, tin oxide, or zinc oxide. When a metal oxide is used as the conductive particles, the surface of the metal oxide may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum or an oxide thereof. The conductive particles may have a laminated structure having a core particle and a coating layer that covers the core particle. Examples of the core particle include titanium oxide, barium sulfate, zinc oxide, etc. Examples of the coating layer include metal oxides such as tin oxide. Furthermore, when a metal oxide is used as the conductive particles, the volume average particle size thereof is preferably 1 nm or more and 500 nm or less, and more preferably 3 nm or more and 400 nm or less. Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, and alkyd resin. The conductive layer may further contain silicone oil, resin particles, a masking agent such as titanium oxide, and the like.
[0019] The thickness of the conductive layer is preferably from 1 μm to 50 μm, and particularly preferably from 3 μm to 40 μm. The conductive layer can be formed by preparing a coating solution for the conductive layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of the dispersion method for dispersing the conductive particles in the coating solution for the conductive layer include a method using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser.
[0020] <Undercoat layer> In the present disclosure, an undercoat layer may be provided on the support or the conductive layer. By providing an undercoat layer, the adhesion function between layers can be improved and a charge injection blocking function can be imparted. The undercoat layer preferably contains a resin. Alternatively, the undercoat layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group. Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl phenol resin, alkyd resin, polyvinyl alcohol resin, polyethylene oxide resin, polypropylene oxide resin, polyamide resin, polyamic acid resin, polyimide resin, polyamideimide resin, and cellulose resin. Examples of the polymerizable functional group contained in the monomer having a polymerizable functional group include an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxyl group, an amino group, a carboxy group, a thiol group, a carboxylic anhydride group, and a carbon-carbon double bond group.
[0021] For the purpose of improving electrical properties, the undercoat layer may further contain an electron transporting material, a metal oxide, a metal, a conductive polymer, etc. Among these, it is preferable to use an electron transporting material or a metal oxide. Examples of the electron transport substance include a quinone compound, an imide compound, a benzimidazole compound, a cyclopentadienylidene compound, a fluorenone compound, a xanthone compound, a benzophenone compound, a cyanovinyl compound, an aryl halide compound, a silole compound, a boron-containing compound, etc. An electron transport substance having a polymerizable functional group may be used as the electron transport substance, and the undercoat layer may be formed as a cured film by copolymerizing the electron transport substance with the monomer having the polymerizable functional group described above. Examples of metal oxides include indium tin oxide, tin oxide, indium oxide, titanium oxide, zinc oxide, aluminum oxide, silicon dioxide, etc. Examples of metals include gold, silver, aluminum, etc. The undercoat layer may further contain an additive.
[0022] The thickness of the undercoat layer is preferably from 0.1 μm to 50 μm, more preferably from 0.2 μm to 40 μm, and particularly preferably from 0.3 μm to 30 μm. The undercoat layer can be formed by preparing a coating solution for the undercoat layer containing the above-mentioned materials and solvent, forming a coating film from the coating solution, and drying and / or curing the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0023] <Photosensitive layer> The photosensitive layer of an electrophotographic photoreceptor is mainly classified into (1) a laminated type photosensitive layer and (2) a single-layer type photosensitive layer. (1) The laminated type photosensitive layer has a charge generation layer containing a charge generation material and a charge transport layer containing a charge transport material. (2) The single-layer type photosensitive layer has a photosensitive layer containing both a charge generation material and a charge transport material. In the present disclosure, the surface layer refers to the charge transport layer in the case of (1) and the single-layer type photosensitive layer itself in the case of (2).
[0024] (1) Laminated photosensitive layer The laminated type photosensitive layer has a charge generating layer and a charge transport layer.
[0025] (1-1) Charge generation layer The charge generating layer preferably contains a charge generating material and a resin. Examples of the charge generating material include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among these, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred. The content of the charge generating material in the charge generating layer is preferably from 40% by mass to 85% by mass, and more preferably from 60% by mass to 80% by mass, based on the total mass of the charge generating layer. Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, polyvinyl butyral resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl alcohol resin, cellulose resin, polystyrene resin, polyvinyl acetate resin, polyvinyl chloride resin, etc. Among these, polyvinyl butyral resin is preferable.
[0026] The charge generating layer may further contain additives such as an antioxidant and an ultraviolet absorbing agent, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, and benzophenone compounds. The thickness of the charge generating layer is preferably from 0.1 μm to 1 μm, and more preferably from 0.15 μm to 0.4 μm. The charge generating layer can be formed by preparing a coating solution for the charge generating layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0027] (1-2) Charge transport layer The charge transport layer (surface layer) preferably contains a charge transport material and a resin. Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred because they have a high effect of suppressing the generation of black spots.
[0028] As examples of preferred charge transport materials, structures of CTM1 to CTM10 are shown below. [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka]
[0029] The content of the charge transport material in the charge transport layer is preferably from 25% by weight to 70% by weight, and more preferably from 30% by weight to 55% by weight, based on the total weight of the charge transport layer.
[0030] In the present disclosure, the charge transport layer contains a polycarbonate resin having a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structural unit represented by the following formula (3). [ka] [ka] [ka]
[0031] In addition, in the present disclosure, the polymer component recovered from the charge transport layer is subjected to pyrolysis gas chromatography mass spectrometry in the presence of tetramethylammonium hydroxide (TMAH), and the total ion chromatogram (TIC) obtained has the following mass spectrum: That is, the TIC has a mass spectrum including components at m / z=242 and m / z=227, and a mass spectrum including components at m / z=296, m / z=253, m / z=145, and m / z=121. Furthermore, the polymer component was analyzed using deuterated chloroform. 1 The H-nuclear magnetic resonance spectrum (NMR spectrum) has peaks at 2.35±0.02 ppm and 2.40±0.02 ppm.
[0032] The fact that the TIC has a mass spectrum including components at m / z=242 and m / z=227 corresponds to the polycarbonate resin contained in the charge transport layer having at least one of the structural units represented by the above formula (2) and the structural units represented by the above formula (3). In addition, the fact that the TIC has a mass spectrum including components at m / z=296, m / z=253, m / z=145, and m / z=121 corresponds to the polycarbonate resin contained in the charge transport layer having the structural unit represented by the above formula (1).
[0033] Also, 1 The H-NMR spectrum having a peak at 2.35±0.02 ppm corresponds to the polycarbonate resin contained in the charge transport layer having the structural unit represented by the above formula (2). 1 The 1 H-NMR spectrum having a peak at 2.40±0.02 ppm corresponds to the polycarbonate resin contained in the charge transport layer having the structural unit represented by the above formula (3).
[0034] In the above polycarbonate resin, the content ratio of the structural unit represented by formula (2) is preferably 40 mol % or more and 60 mol % or less based on the total content of the structural unit represented by formula (2) and the content of the structural unit represented by formula (3).
[0035] In addition, in the above polycarbonate resin, the total content ratio of the structural unit represented by formula (2) and the structural unit represented by formula (3) is preferably 40 mol % or more and 60 mol % or less relative to the total content of the structural unit represented by formula (1), the content of the structural unit represented by formula (2), and the content of the structural unit represented by formula (3).
[0036] A specific example of a technique for recovering the polymer component from the charge transport layer, and for subjecting the recovered polymer component to pyrolysis gas chromatography mass spectrometry (pyrolysis GCMS) and NMR measurement will be described below.
[0037] <Recovery of polymer components from charge transport layer> The polymer component is recovered from the charge transport layer by reprecipitation of the resin in the charge transport layer according to the following procedure. 1. Cut the electrophotographic photoreceptor The electrophotographic photosensitive member is cut with a jigsaw at a position 10 cm from the end of the electrophotographic photosensitive member in the generatrix direction. 2. Wash the inside of the cut 10 cm electrophotographic photoconductor The inner surface of the electrophotographic photoreceptor is wiped with Silbon paper soaked in chloroform. 3. Dissolve the charge transport layer The cut end of the electrophotographic photosensitive member is immersed in chloroform for 3 cm. Specifically, pour approximately 60cc of chloroform into a 100mL beaker and immerse it at room temperature for 5 minutes. 4. Concentrate (concentrate liquefaction) Concentrate to 2 mL using a rotary evaporator. 5. Re-sedimentation Prepare 50 mL of a methanol / acetone mixture (volume ratio 1:1) and dropwise add the entire amount of the above concentrated solution while stirring. 6. Filter A filter paper (No. 5C-40, manufactured by Kiriyama Seisakusho Co., Ltd.) is placed in a Kiriyama funnel (SU-40, manufactured by Kiriyama Seisakusho Co., Ltd.) and suction filtration is performed. 7. Dry The residue on the filter paper is collected with a spatula and dried in vacuum (70°C, 1 hour).
[0038] <Pyrolysis GCMS> Equipment configuration: Pyrolysis equipment + gas chromatography (GC) equipment + mass spectrometry (MS) equipment Pyrolysis equipment: Japan Analytical Industry Co., Ltd. JPS-700 GC equipment: Thermo Fisher Scientific FOCUS-GC MS device: ISQ manufactured by Thermo Fisher Scientific Co., Ltd. Sample amount: 0.1 mg (contains TMAH (manufactured by Tama Chemicals Co., Ltd.)) Thermal decomposition temperature: 590°C (using Pyrofoil F590 manufactured by Japan Analytical Industry Co., Ltd.) Column: "HP5-MS" (Agilent Technologies, Inc. 19091S-433, length 30 m, inner diameter 0.25 mm, film thickness 0.25 μm) GC injection port conditions: Inlet Temp: 250 °C Split Flow: 50 mL / min GC temperature rising conditions: 40 °C (5 min) → 10 °C / min (300 °C) → 300 °C (20 min) MS conditions: Ion Source Temp: 200 °C MS Transfer Line Temp: 250 °C
[0039] <NMR measurement> · Preparation of measurement sample Dissolve 20 mg of the sample in 1 g of deuterated chloroform containing the reference substance tetramethylsilane, and transfer the whole amount to an NMR tube. As the deuterated chloroform, for example, deuterated chloroform (manufactured by Sigma-Aldrich Japan Co., Ltd., chloroform-d, model number 612200) can be used. As the NMR tube, an NMR tube (manufactured by Norell, ST500-7, model number S3010) can be used. · NMR measurement Apparatus: Bruker AVANCE500 Conditions: Proton NMR, automatic measurement by ICON-NMR Number of integrations: 32 times Reference peak: Set the methyl group peak of tetramethylsilane to 0 ppm
[0040] The content ratio of the charge transport material to the resin (charge transport material: resin) is preferably in the range of 4:10 to 20:10 by mass ratio, and more preferably in the range of 5:10 to 10:10.
[0041] In addition, the charge transport layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipperiness imparting agents, and wear resistance improving agents. Specifically, the additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, boron nitride particles, etc. Among these, silica particles are preferred from the viewpoint of scratch resistance. In addition, the volume average particle size of the silica particles is preferably 0.1 μm or more and 0.5 μm or less, because the charge transport layer in the configuration according to the present disclosure can easily absorb external impacts and suppress scratches.
[0042] The thickness of the charge transport layer is preferably from 5 μm to 50 μm, more preferably from 8 μm to 40 μm, and particularly preferably from 10 μm to 30 μm. The charge transport layer can be formed by preparing a coating solution for the charge transport layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Among these solvents, ether-based solvents or aromatic hydrocarbon-based solvents are preferred.
[0043] (2) Single-layer photosensitive layer The single-layer type photosensitive layer can be formed by preparing a coating solution for the photosensitive layer containing a charge generating material, a charge transporting material, a resin, and a solvent, forming a coating film of this, and drying it. The charge generating material, the charge transporting material, and the resin are the same as the examples of materials in the above "(1) Laminated type photosensitive layer". The single-layer type photosensitive layer is a surface layer, and contains a polycarbonate resin having a structural unit represented by formula (1), a structural unit represented by formula (2), and a structural unit represented by formula (3) as described in the above "(1-2) Charge transporting layer".
[0044] Next, the toner used in the configuration according to the present disclosure will be described in detail below. <Toner manufacturing method> A method for producing the toner particles will now be described. The toner particles can be produced by known methods, such as a kneading and grinding method or a wet production method. From the viewpoint of uniform particle size and shape controllability, a wet production method is preferably used. Further, examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, and an emulsion aggregation method, and the emulsion aggregation method is preferably used. In the emulsion aggregation method, first, materials such as binder resin particles and colorant particles are dispersed and mixed in an aqueous medium containing a dispersion stabilizer. A surfactant may be added to the aqueous medium. Then, an aggregating agent is added to aggregate the particles to a desired toner particle size, and then or simultaneously with the aggregation, the resin particles are fused together. If necessary, the shape is controlled by heat to form toner particles. Here, the binder resin particles can be composite particles formed of two or more layers made of resins with different compositions. For example, they can be produced by emulsion polymerization, mini-emulsion polymerization, phase inversion emulsification, or a combination of several production methods. When an internal additive such as a colorant is contained in the toner particles, the internal additive may be contained in the resin particles. Alternatively, a dispersion liquid of internal additive particles consisting only of the internal additive may be separately prepared, and the internal additive particles may be aggregated together with the resin particles when the resin particles are aggregated. Furthermore, by adding resin particles having different compositions at different times during aggregation and then aggregating the resin particles, it is possible to produce toner particles having layer structures with different compositions.
[0045] The following can be used as the dispersion stabilizer. Examples of inorganic dispersion stabilizers include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Examples of the organic dispersion stabilizer include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.
[0046] As the surfactant, a known cationic surfactant, anionic surfactant, or nonionic surfactant can be used. Specific examples of the cationic surfactant include dodecyl ammonium bromide, dodecyl trimethyl ammonium bromide, dodecyl pyridinium chloride, dodecyl pyridinium bromide, and hexadecyl trimethyl ammonium bromide. Specific examples of nonionic surfactants include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, sorbitan monooleate polyoxyethylene ether, styrylphenyl polyoxyethylene ether, and monodecanoyl sucrose. Specific examples of anionic surfactants include aliphatic soaps such as sodium stearate and sodium laurate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and sodium polyoxyethylene (2) lauryl ether sulfate.
[0047] <Binding resin> The binder resin constituting the toner particles will be described. Suitable examples of the binder resin include vinyl resins and polyester resins. Examples of the vinyl resin, polyester resin, and other binder resins include the following resins or polymers. Homopolymers of styrene and its substituted derivatives such as polystyrene and polyvinyltoluene; styrene-based copolymers such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resins, polyamide resins, epoxy resins, polyacrylic resins, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or alicyclic hydrocarbon resins, and aromatic petroleum resins. These binder resins can be used alone or in combination.
[0048] The binder resin preferably contains a carboxy group, and is preferably a resin produced using a polymerizable monomer containing a carboxy group. For example, vinyl carboxylic acids such as acrylic acid, methacrylic acid, α-ethyl acrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives such as succinic acid monoacryloyloxyethyl ester, succinic acid monomethacryloyloxyethyl ester, phthalic acid monoacryloyloxyethyl ester, and phthalic acid monomethacryloyloxyethyl ester.
[0049] The polyester resin may be a condensation polymer of a carboxylic acid component and an alcohol component as listed below. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. Examples of the alcohol component include bisphenol A, hydrogenated bisphenol, an ethylene oxide adduct of bisphenol A, a propylene oxide adduct of bisphenol A, glycerin, trimethylolpropane, and pentaerythritol. The polyester resin may be a polyester resin containing a urea group. It is preferable that the carboxyl groups at the terminals of the polyester resin are not capped.
[0050] <Crosslinking agent> In order to control the molecular weight of the binder resin constituting the toner particles, a crosslinking agent may be added during polymerization of the polymerizable monomer. For example, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloyloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester type diacrylate (MANDA Nippon Kayaku), and those in which the above acrylates have been replaced with methacrylates. The amount of the crosslinking agent added is preferably 0.001 parts by mass or more and 15,000 parts by mass or less based on 100 parts by mass of the polymerizable monomer.
[0051] <Release agent> It is preferable that the toner particles contain a release agent as one of the materials constituting the toner particles. In particular, when an ester wax having a melting point of 60° C. to 90° C. is used as the release agent, it is easy to obtain a plasticizing effect because of its excellent compatibility with the binder resin. Examples of the ester wax include waxes mainly composed of fatty acid esters, such as carnauba wax and montan acid ester wax; and fatty acid esters from which some or all of the acid components have been deoxidized, such as deoxidized carnauba wax; methyl ester compounds having a hydroxy group obtained by, for example, hydrogenation of vegetable oils and fats; saturated fatty acid monoesters, such as stearyl stearate and behenyl behenate; diesters of saturated aliphatic dicarboxylic acids and saturated aliphatic alcohols, such as dibehenyl sebacate, distearyl dodecanedioate, and distearyl octadecanedioate; and diesters of saturated aliphatic diols and saturated aliphatic monocarboxylic acids, such as nonanediol dibehenate and dodecanediol distearate.
[0052] Among these waxes, it is preferable to use a bifunctional ester wax (diester) having two ester bonds in the molecular structure. The difunctional ester wax is an ester compound of a dihydric alcohol and an aliphatic monocarboxylic acid, or an ester compound of a dihydric carboxylic acid and an aliphatic monoalcohol. Specific examples of the aliphatic monocarboxylic acid include myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, oleic acid, vaccenic acid, linoleic acid, and linolenic acid. Specific examples of the aliphatic monoalcohol include myristyl alcohol, cetanol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, and triacontanol. Specific examples of divalent carboxylic acids include butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), heptanedioic acid (pimelic acid), octanedioic acid (suberic acid), nonanedioic acid (azelaic acid), decanedioic acid (sebacic acid), dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, phthalic acid, isophthalic acid, and terephthalic acid. Specific examples of dihydric alcohols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosanediol, 1,30-triacontanediol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiroglycol, 1,4-phenylene glycol, bisphenol A, and hydrogenated bisphenol A.
[0053] Other usable release agents include petroleum waxes such as paraffin wax, microcrystalline wax, and petrolatum and derivatives thereof, montan wax and derivatives thereof, hydrocarbon waxes produced by the Fischer-Tropsch process and derivatives thereof, polyolefin waxes such as polyethylene and polypropylene and derivatives thereof, natural waxes such as carnauba wax and candelilla wax and derivatives thereof, higher aliphatic alcohols, fatty acids such as stearic acid and palmitic acid, and compounds thereof. The content of the release agent is preferably 5.0 parts by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer.
[0054] <Coloring agent> When a colorant is contained in the toner particles, there is no particular limitation, and any known colorant including the examples shown below can be used.
[0055] Examples of yellow pigments that can be used include condensed azo compounds such as yellow iron oxide, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include the following. CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, 180.
[0056] Examples of red pigments include condensed azo compounds such as red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red C, lake red D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, and alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include the following. CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254.
[0057] Examples of blue pigments include alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, copper phthalocyanine compounds such as indanthrene blue BG and their derivatives, anthraquinone compounds, basic dye lake compounds, etc. Specific examples include the following. CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66.
[0058] Examples of black pigments include carbon black and aniline black. These colorants can be used alone or in combination, or in the form of a solid solution. The content of the colorant is preferably 3.0 parts by mass or more and 15.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or polymerizable monomer.
[0059] <Charge control agents and charge control resins> The toner particles may contain a charge control agent. Any known charge control agent can be used as the charge control agent. In particular, a charge control agent that can charge quickly and stably maintain a constant charge amount is preferred.
[0060] As the charge control agent that controls the toner particles to have a negative charge, the following can be mentioned. Organometallic compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. Other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.
[0061] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: modified nigrosine, guanidine compounds, imidazole compounds, quaternary ammonium salts such as tributylbenzylammonium 1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts that are analogues of these, and lake pigments thereof, triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.), metal salts of higher fatty acids, and resin-based charge control agents.
[0062] The charge control agents may be contained alone or in combination of two or more kinds. The content of the charge control agent is preferably 0.01 parts by mass or more and 10.00 parts by mass or less with respect to 100.00 parts by mass of the binder resin or polymerizable monomer.
[0063] <External additives> The toner of the present disclosure contains particles of a silicon atom-containing compound as an external additive. As the silicon atom-containing compound, organosilicon particles and silica particles are preferred. The external additive preferably contains hydrotalcite particles. Particles of hydrotalcite are generally represented by the following formula (HT). M 2+ y M 3+ x (OH)2A n- (x / n) ·mH2O formula (HT) where 0 <x≦0.5、y=1-x、m≧0である。 Said M 2+ and M 3+ represent divalent and trivalent metals, respectively. M 2+ is preferably at least one divalent metal ion selected from the group consisting of Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe. 3+is preferably at least one trivalent metal ion selected from the group consisting of Al, B, Ga, Fe, Co, and In. 2+ is Mg and M 3+ is preferably Al. A n- is an anion with a valence of n. n- As for CO3 2- , O.H. - , Cl - , I - , F - , Br - , SO4 2- , HCO3 - , CH3COO - , and NO3 - Any one of these may be present alone, or a plurality of these may be present at the same time. The hydrotalcite particles preferably have fluorine atoms. The method for preparing the hydrotalcite particles having fluorine atoms is not particularly limited, and examples thereof include a method of treating the hydrotalcite particles using a coupling treatment agent having fluorine atoms or in an aqueous solution containing fluoride ions. From the viewpoint of uniform treatment, a method of wet treating the hydrotalcite particles in an aqueous solution containing fluoride ions is preferred. In the present disclosure, the divalent metal ion M 2+ It is preferable that the trivalent metal ion M 3+ That is, in the present disclosure, the hydrotalcite particles preferably contain fluorine atoms, magnesium atoms, and aluminum atoms.
[0064] [Process cartridges, electrophotographic devices] The process cartridge according to the present disclosure integrally supports the electrophotographic photosensitive member, developing means, and cleaning means described above, and is detachably mountable to the main body of the electrophotographic apparatus. Moreover, the electrophotographic apparatus according to the present disclosure includes the process cartridge according to the present disclosure.
[0065] FIG. 1 shows an example of the schematic configuration of an electrophotographic apparatus having a process cartridge equipped with the above-mentioned electrophotographic photosensitive member. A cylindrical electrophotographic photoreceptor 1 is rotated around an axis 2 in the direction of the arrow at a predetermined peripheral speed. The surface of the electrophotographic photoreceptor 1 is charged to a predetermined positive or negative potential by charging means 3. Note that, although a roller charging method using a roller-type charging member is shown in FIG. 1, other charging methods such as a corona charging method, a proximity charging method, and an injection charging method may also be used. Exposure light 4 is irradiated from an exposure means (not shown) onto the charged surface of the electrophotographic photoreceptor 1, and an electrostatic latent image corresponding to the target image information is formed. The electrostatic latent image formed on the surface of the electrophotographic photoreceptor 1 is developed with toner contained in a development means 5, and a toner image is formed on the surface of the electrophotographic photoreceptor 1. The toner image formed on the surface of the electrophotographic photoreceptor 1 is transferred to a transfer material 7 by a transfer means 6. The transfer material 7 onto which the toner image has been transferred is transported to a fixing means 8, where the toner image is fixed, and the resulting image is printed out from the electrophotographic apparatus. The process cartridge 11 has a cleaning means 9 for cleaning the toner and other deposits remaining on the surface of the electrophotographic photoreceptor 1 after transfer with a cleaning blade. The contact force per unit length in the longitudinal direction of the cleaning blade against the surface of the electrophotographic photoreceptor 1 is preferably 0.196 N / cm or more and 0.490 N / cm or less. If the contact force is 0.196 N / cm or more, high cleaning performance can be obtained in the combination of the electrophotographic photoreceptor 1 and the toner described above. Furthermore, if the contact force is 0.490 N / cm or less, wear on the surface of the electrophotographic photoreceptor 1 and damage to the cleaning blade can be suppressed. The electrophotographic apparatus may have a charge removing mechanism that removes charge from the surface of the electrophotographic photoreceptor 1 by pre-exposure light 10 from a pre-exposure means (not shown). In addition, a guide means 12 such as a rail may be provided in order to mount and remove the process cartridge 11 of the present disclosure to and from the main body of the electrophotographic apparatus. The process cartridge 11 according to the present disclosure can be used in laser beam printers, LED printers, copiers, and the like. EXAMPLES
[0066] The present disclosure will be described in more detail below using examples and comparative examples. The present disclosure is not limited in any way by the following examples, as long as it does not exceed the gist of the disclosure. In the following description of the examples, "parts" are based on mass unless otherwise specified. Hereinafter, the electrophotographic photoreceptor may also be simply referred to as a photoreceptor.
[0067] <Production of Support and Coating Liquid for Each Layer of Electrophotographic Photoreceptor> [Preparation of the support] A cylinder made of aluminum alloy (JIS-A3003, aluminum alloy) with a rough cut surface and an outer diameter of 24 mm, a length of 261 mm, and a thickness of 0.9 mm was mounted on an NC lathe. A support was then fabricated by cutting the diamond sintered tool while changing the contact angle of the diamond sintered tool with respect to the raw tube between 0° and 3° so that the outer diameter was 23.97 mm and the surface roughness Ra (S80) was 0.02 μm. The tool cutting was performed by setting the spindle speed of the lathe to 3000 rpm and varying the tool movement speed (tool feed speed) by a program that repeatedly increases and decreases the feed speed. The tool feed speed was changed between 0.340 and 0.360 mm / revolution by 0.005 mm / revolution for every 1.5 mm of processing distance. The ΔL on the outer peripheral surface of the support was measured and found to be 50 μm. Here, ΔL was obtained by measuring the roughness of the cross-sectional curve near the center of the outer peripheral surface of the support. The roughness was measured using a "Surfcom 1400D" (manufactured by Tokyo Seimitsu Co., Ltd.) under the measurement conditions of JIS1994 standard: measurement length 4.0 mm, long wavelength cutoff λc 0.8 mm (Gaussian), and measurement speed 0.3 mm / sec. Furthermore, Ra (S80) is the arithmetic mean roughness Ra obtained by measuring the roughness of the central area of the outer peripheral surface of the support using a "Surfcom 1400D" (manufactured by Tokyo Seimitsu Co., Ltd.) The roughness measurement was performed under the following measurement conditions according to the JIS'01 standard: measurement length 4.0 mm, long wavelength cutoff λc 0.8 mm (Gaussian), short wavelength cutoff λs 80 μm, and measurement speed 0.3 mm / sec.
[0068] [Preparation of coating solution for undercoat layer] The coating solution for the undercoat layer was prepared as follows. Rutile-type titanium oxide with an average primary particle size of 40 nm (product name: TTO55N, manufactured by Ishihara Sangyo Kaisha) and 3% by mass of methyldimethoxysilane (product name: TSL8117, manufactured by Toshiba Silicones) based on the titanium oxide were mixed in a Henschel mixer to obtain a surface-treated titanium oxide. The surface-treated titanium oxide was then dispersed in a mixed solvent of methanol / 1-propanol with a mass ratio of 7 / 3 using a ball mill to obtain a dispersion slurry of the surface-treated titanium oxide. The obtained dispersion slurry, a mixed solvent of methanol / 1-propanol / toluene, and the copolymerized polyamide pellets were stirred and mixed while heating to dissolve the polyamide pellets. The copolymerized polyamide was composed of the following five components, and the molar composition ratios of each component were as follows: ε-caprolactam represented by the following formula (D): 60% Bis(4-amino-3-methylcyclohexyl)methane represented by the following formula (E): 15% Hexamethylenediamine represented by the following formula (F): 5% Decamethylenedicarboxylic acid represented by the following formula (G): 15% Octadecamethylenedicarboxylic acid represented by the following formula (H): 5% Then, ultrasonic dispersion treatment was performed to prepare a coating solution for an undercoat layer having a solid content of 18.0%. The obtained coating solution for an undercoat layer contained surface-treated titanium oxide / copolymerized polyamide in a mass ratio of 3 / 1 in a mixed solvent of methanol / 1-propanol / toluene (mass ratio of 7 / 1 / 2). [ka] [ka] [ka] [ka]
[0069] [Preparation of Coating Solution for Charge Generation Layer] As a charge generating material, 10 parts of Y-type oxytitanium phthalocyanine crystals having a strong peak at 27.3° of the Bragg angle (2θ±0.2°) in CuKα characteristic X-ray diffraction were prepared. This charge generating material and 150 parts of 4-methoxy-4-methyl-2-pentanone were placed in a sand mill using glass beads with a diameter of 1 mm, and ground and dispersed by the sand grinding mill for 1.5 hours. Next, 105 parts of a solution in which 5 parts of polyacetal resin (trade name: S-LEC BX-1, manufactured by Sekisui Chemical Co., Ltd.) were dissolved in 100 parts of 4-methoxy-4-methyl-2-pentanone were added to the sand mill, and dispersed for 0.5 hours. Then, 250 parts of 1,2-dimethoxyethane were further added to the sand mill to prepare a coating solution for the charge generating layer. The X-ray diffraction measurements were carried out under the following conditions.
[0070] [Powder X-ray diffraction measurement] Measuring device used: Rigakuden machine RINT-TTRII X-ray Diffraction System, manufactured by X-ray tube:Cu Tube voltage: 50KV Tube current: 300mA Scan method: 2θ / θ scan Scan speed: 4.0° / min Sampling interval: 0.02° Start angle (2θ): 5.0° Stop angle (2θ): 40.0° Attachment: Standard sample holder Filter: Not used Incident Monochromator: Used Counter monochromator: Not used Divergence slit: open Divergence vertical limit slit: 10.00mm Scattering slit: open Receiving slit: open Flat plate monochromator: in use Counter: Scintillation counter
[0071] [Example of polycarbonate resin production] <Production example of polycarbonate resin P1> The following materials were prepared: Compound represented by the following formula (B-1): 677.00 g (2.52 mol) Compound represented by the following formula (B-2): 180.18 g (0.84 mol) Compound represented by the following formula (B-3): 180.18 g (0.84 mol) Triethylbenzylammonium chloride: 0.4g Hydrosulfite: 5.0g These were dissolved in 5.4 L of 9.0 w / w% aqueous sodium hydroxide (NaOH). 2.4 L of methylene chloride was added to this, and while stirring, 540 g of phosgene was blown in over 30 minutes while maintaining the temperature at 15°C. After the blowing in of phosgene was completed, 21 g of pt-butylphenol was added and the reaction liquid was emulsified by vigorous stirring. After the emulsification, 11 ml of triethylamine was added, and the mixture was stirred at a temperature of 20 to 25°C for about 1 hour to polymerize. After the polymerization was completed, the reaction solution was separated into an aqueous phase and an organic phase, and the organic phase was neutralized with phosphoric acid. The organic phase was repeatedly washed with water until the conductivity of the washing water was 10 μS / cm or less. The obtained organic phase was dropped into hot water kept at 62°C, and the solvent was evaporated and removed to obtain a white powdery precipitate. The obtained precipitate was filtered and dried at a temperature of 120°C for 24 hours to obtain the target polycarbonate resin P1. [ka] [ka] [ka] [ka]
[0072] <Production examples of polycarbonate resins P2 to P18> Polycarbonate resin P1 was produced in the same manner as in Production Example of Polycarbonate Resin P1, except that the copolymerization units of the polycarbonate resin used were changed to the compounds shown in Table 1 and used in the molar ratios shown in Table 1.
[0073] [Table 1]
[0074] [Preparation of Coating Solution 1 for Charge Transport Layer] The following materials were prepared: Charge transport material (hole transport material) CTM10: 10 parts Polycarbonate resin (P1): 10 parts These were dissolved in a mixed solvent of 55 parts of toluene and 45 parts of tetrahydrofuran to prepare coating solution 1 for the charge transport layer.
[0075] [Preparation of Coating Solutions 2 to 19 for Charge Transport Layer] The charge transport layer coating solution was prepared in the same manner as in Coating Solution 1, except that the type and amount of polycarbonate resin was changed as shown in Table 2.
[0076] [Table 2]
[0077] <Preparation of Electrophotographic Photoreceptor> [Preparation of photoreceptor 1] The coating liquid for forming an undercoat layer prepared above was dip-coated on a support, and dried at 100° C. for 10 minutes to provide an undercoat layer with a thickness of 2.0 μm. The charge generating layer coating liquid prepared above was dip coated on the resulting undercoat layer, and dried at 100° C. for 10 minutes to provide a charge generating layer having a thickness of 0.15 μm. The charge transport layer coating solution 1 prepared above was dip-coated on the resulting charge generation layer, and dried at 120° C. for 30 minutes to provide a charge transport layer having a thickness of 16.0 μm. In this manner, photoreceptor 1 was prepared.
[0078] [Photoconductor 2~19] Photoreceptors 2 to 19 were prepared in the same manner as in the preparation of photoreceptor 1, except that the type of coating liquid for the charge transport layer used was changed as shown in Table 3.
[0079] [Table 3]
[0080] <Toner manufacturing example> The production examples of the toner used in the examples and comparative examples will be described below. In the examples of the present disclosure, toner particles produced by an emulsion polymerization aggregation method are used, but the toner particles in the present disclosure are not necessarily limited to this, and any toner particles obtained by a pulverization method, a suspension polymerization method, or a solution suspension method can be used.
[0081] <Preparation of Colorant Dispersion> Carbon black (specific surface area by BET method: 60 m 2 50 parts by mass of a colorant dispersion (1 / g), 3 parts by mass of an anionic surfactant (Neogen RK, Daiichi Kogyo Seiyaku), and 400 parts by mass of ion-exchanged water were mixed together. The resulting mixture was dispersed using a homogenizer (IKA: Ultra Turrax) to obtain a colorant dispersion.
[0082] <Preparation of Resin Particle Dispersion> Non-ionic surfactant (Sanyo Chemical Industries, Ltd.: Nonipol) and 10 parts by mass of an anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.: Neogen RK) were dissolved in 520 parts by mass of ion-exchanged water to prepare a surfactant solution. The above surfactant solution, 280 parts by mass of styrene, 100 parts by mass of n-butyl acrylate, 7 parts by mass of acrylic acid, and 15 parts by mass of a charge control agent Bontron E-88 (manufactured by Orient Chemical Co., Ltd.) were mixed and dissolved in advance, and a solution prepared by dissolving the above surfactant solution was added to a flask and emulsified. While slowly mixing for 10 minutes, 70 parts by mass of ion-exchanged water in which 3 parts by mass of ammonium persulfate were further added. After sufficient nitrogen replacement, the flask was heated in an oil bath while stirring until the contents reached 70°C, and emulsion polymerization was continued for 6 hours. Thereafter, the reaction solution was cooled to room temperature and the weight average particle size (D4) was 150 nm and the glass transition temperature was 100° C. Transfer A resin particle dispersion liquid having a temperature of 57.0°C was obtained. The weight average particle size was measured using a Microtrack particle size distribution measuring instrument (manufactured by Nikkiso Co., Ltd.) Measurements using this Microtrack particle size distribution measuring instrument were performed under the conditions of a measurement range of 0.12 to 704 μm, a measurement time of 30 seconds, and a medium of ion-exchanged water.
[0083] <Preparation of release agent dispersion> As a release agent, 200 parts by mass of pentaerythritol behenic acid, 3 parts by mass of an anionic surfactant (Paionin A-45-D manufactured by Takemoto Oil Co., Ltd.), and 700 parts by mass of ion-exchanged water were mixed. The resulting mixture was dispersed using a homogenizer (Ultra Turrax manufactured by IKA Co., Ltd.), and a dispersion treatment was carried out using a pressure discharge type homogenizer, to obtain a release agent dispersion liquid.
[0084] <Production of toner particles> The following materials were prepared: ·300 parts by mass of resin particle dispersion Colorant dispersion 200 parts by weight Release agent dispersion 100 parts by weight Cationic surfactant (Kao Corporation: Sanisol B50) 3 parts by weight Ion-exchanged water 500 parts by weight The above components were mixed and dispersed in a round-bottom stainless steel flask using a homogenizer (Ultra Turrax T50, manufactured by IKA). The pH was then adjusted, and the mixture was heated to 50°C in a heating oil bath while stirring, and held at 50°C for 30 minutes to form aggregated particles. 30 parts of the resin particle dispersion was added to this aggregated particle liquid, and the mixture was heated and stirred at 50°C for another 3 hours. Next, 6 parts of sodium dodecylbenzenesulfonate (Neogen SC, manufactured by Daiichi Kogyo Co., Ltd.), an anionic surfactant, was added to this dispersion liquid, heated to 95°C, and maintained for 9 hours to fuse the aggregated particles. Thereafter, the mixture was cooled to 50°C at a rate of decrease of 0.3°C / min, filtered, and thoroughly washed with ion-exchanged water. Thereafter, the mixture was filtered through a 400 mesh sieve to obtain fused particles. The obtained fused particles were dried in a vacuum dryer to obtain toner particles.
[0085] <Preparation of external additives> As the external additives, the following commercially available products and those prepared as follows were used.
[0086] <External additive 1> Silica particles (RX200: average primary particle size 12 nm, HMDS treatment, manufactured by Nippon Aerosil Co., Ltd.) were used as external additive 1.
[0087] <Preparation of external additive 2> Metatitanic acid produced by the sulfuric acid method was deironized and bleached, then 3 mol / L sodium hydroxide solution was added to adjust the pH to 9.0 and desulfurized. It was then neutralized to pH 5.6 with 5 mol / L hydrochloric acid, filtered and washed with water. Water was added to the washed cake to make a slurry of 1.90 mol / L TiO2, and hydrochloric acid was added to adjust the pH to 1.4 and peptized. The metatitanic acid that had been desulfurized and peptized was collected in an amount of 1.90 moles in terms of TiO2 and placed in a 3L reaction vessel. A strontium chloride aqueous solution was added to the peptized metatitanic acid slurry so that the SrO / TiO2 (molar ratio) was 1.15 and the SrO was 2.185 moles, and the TiO2 concentration was then adjusted to 1.039 moles / L. Next, the mixture was heated to 90°C while stirring and mixing, and 440 mL of a 10 mole / L sodium hydroxide aqueous solution was added over 40 minutes. After that, the mixture was stirred for 45 minutes at 95°C, and then placed in ice water to rapidly cool and terminate the reaction. The reaction slurry was heated to 70° C., and 12 mol / L hydrochloric acid was added until the pH reached 5.0, followed by stirring for 1 hour, and the resulting precipitate was decanted. The slurry containing the obtained precipitate was adjusted to 40°C, and hydrochloric acid was added to adjust the pH to 2.5. Then, 4.6% by mass of isobutyltrimethoxysilane and 4.6% by mass of trifluoropropyltrimethoxysilane were added based on the solid content and stirred for 10 hours. After adjusting the pH to 6.5 by adding 5 mol / L aqueous sodium hydroxide solution and continuing stirring for 1 hour, the mixture was filtered and washed, and the resulting cake was dried in the air at 120°C for 8 hours and then pulverized to obtain strontium titanate particles. The obtained strontium titanate particles were used as external additive 2.
[0088] <Preparation of external additive 3> A mixed aqueous solution of 1.03 mol / L magnesium chloride and 0.239 mol / L aluminum sulfate (Liquid A), a 0.753 mol / L aqueous solution of sodium carbonate (Liquid B), and a 3.39 mol / L aqueous solution of sodium hydroxide (Liquid C) were prepared. Next, liquid A, liquid B, and liquid C were poured into the reaction tank using a metering pump at a flow rate such that the volume ratio of liquid A:liquid B was 4.5:1, and the pH value of the reaction liquid was maintained in the range of 9.3 to 9.6 using liquid C. The reaction was carried out at 40°C to produce a precipitate. After filtration and washing, the precipitate was re-emulsified in ion-exchanged water to obtain a raw material hydrotalcite slurry. The concentration of hydrotalcite in the obtained hydrotalcite slurry was 5.6% by mass. The obtained hydrotalcite slurry was vacuum dried overnight at 40°C. NaF was dissolved in ion-exchanged water to a concentration of 100mg / L, and a solution was prepared by adjusting the pH to 7.0 using 1mol / L HCl or 1mol / L NaOH, to which the dried hydrotalcite was added to a concentration of 0.1% (w / v%). The mixture was stirred at a constant speed for 48 hours using a magnetic stirrer so as not to cause precipitation. The mixture was then filtered through a membrane filter with a pore size of 0.5μm and washed with ion-exchanged water. The obtained hydrotalcite was vacuum dried overnight at 40°C, and then crushed. The obtained hydrotalcite particles were used as external additive 3.
[0089] <Preparation of external additive 4> An external additive 4 was obtained in the same manner as in the production example of external additive 3, except that ion-exchanged water was used instead of the NaF aqueous solution.
[0090] <Preparation of External Additive 5> In a 200 ml beaker, 43.0 g of RO water and 0.008 g of acetic acid as a catalyst were charged and stirred at 45 ° C. 54.0 g of trimethoxymethylsilane was added and stirred for 1.5 hours to obtain a raw material solution. In a 1000 ml beaker, 70.0 g of RO water, 340.0 g of methanol, and 1.8 g of 25% ammonia water were charged and stirred at 30 ° C. to prepare an alkaline aqueous medium. The raw material solution was dropped into this alkaline aqueous medium over 1 minute. The mixture after the drop of the raw material solution was stirred for 1.5 hours while keeping it at 30 ° C. to proceed with the polycondensation reaction and obtain a polycondensation reaction liquid. In a 2000 ml beaker, 700 g of RO water was charged, and the polycondensation reaction liquid was dropped into it over 10 minutes while stirring at 25 ° C. A propeller with a diameter of φ50 mm was used for stirring, and the rotation speed was set to 200 rpm. The polycondensation reaction liquid became cloudy immediately after mixing with water, yielding a dispersion containing organosilicon polymer particles having siloxane bonds. 23 g of hexamethyldisilazane was added to the dispersion as a hydrophobizing agent and stirred at 60°C for 2.5 hours. The solution was left to stand for 5 minutes, and the powder that had precipitated at the bottom was collected by suction filtration and dried under reduced pressure at 120°C for 24 hours to obtain external additive 5.
[0091] <Production of Toner 1> Toner 1 was obtained by mixing 2.0 parts of external additive 1, 0.25 parts of external additive 2, and 0.30 parts of external additive 3 with respect to 100 parts by mass of toner particles using a Henschel mixer.
[0092] <Production of Toners 2 to 8> Toners 2 to 8 were obtained in the same manner as Toner 1, except that the types and amounts of the external additives used were changed as shown in Table 4. [Table 4]
[0093] [Example 1] The electrophotographic device was a laser beam printer manufactured by Hewlett-Packard (product name: HP Color Laser Jet CP4525 dn The laser beam printer was modified so that it was possible to adjust and measure the voltage applied to the charging roller, adjust and measure the amount of light exposed to an image, and adjust the contact pressure of the cleaning blade against the electrophotographic photosensitive member. In addition, the cyan cartridge was modified, the built-in photoconductor was replaced with Photoconductor 1, and the built-in toner was refilled with Toner 1.
[0094] [Examples 2 to 26, Comparative Examples 1 to 6] Process cartridges according to Examples 2 to 26 and Comparative Examples 1 to 6 were prepared in the same manner as in Example 1, except that the types of photoconductor and toner used in Example 1 were changed as shown in Table 5.
[0095] [evaluation] The process cartridges according to Examples 1 to 26 and Comparative Examples 1 to 6 were used and evaluated under the following conditions.
[0096] ·Fog evaluation The fogging was measured using the above-mentioned evaluation machine as the image forming device. The transfer material used in the durability test was A4 size CLC paper (Canon, Tsubo Amount 80g / m 2The durability test was carried out in a normal temperature and humidity environment (temperature 23.5°C, humidity 60% RH) with a print rate of 1% and a one minute break after every two sheets printed. The test was left for six days after printing 15,000 sheets from the initial stage. After that, the reflectance of the first image sample was measured using a REFLECT O METER MODEL The reflectance was measured using a TC-6DS. Similarly, the transfer paper before the white image formation was left for 6 days and then the reflectance was measured. A green filter was used. The fog was calculated from the reflectance before and after the white image output using the following formula. Fog (reflectance) (%) = Reflectance of transfer paper (%) - Reflectance of white image (%) The evaluation criteria for fog were as follows: C or higher was judged to be good. A: Less than 0.5% B: 0.5% or more but less than 1.5% C: 1.5% or more and less than 3.0% D: 3.0% or more The evaluation results are shown in Table 5.
[0097] -Evaluation of image streaks The charging conditions were a dark potential of -500 V, and the exposure conditions were an image exposure of 0.25 μJ / cm 2 The image was adjusted to the following. Furthermore, evaluation was performed using halftone images immediately after outputting 1,000 sheets of horizontal line images with 10 spaces per line. Specifically, the number of slip-throughs (streaks) that were considered to be due to poor cleaning in the output images was visually counted and ranked. The evaluation criteria for image streaks are as follows: A: There are no streaks in the image quality and the image quality is good. B: Slight streaks are observed. C: Streaks appear in part of the image. D: Streaks appear across the entire image
[0098] The evaluation results are shown in Table 5. [Table 5]
[0099] In Table 5, "C blade" refers to the cleaning blade. In Example 23, the torque was too large, causing chipping of the cleaning blade and resulting in a low evaluation of image streaks.
[0100] Embodiments of the present disclosure include the following configurations. (Configuration 1) A process cartridge which integrally supports an electrophotographic photosensitive member having a surface layer, a developing unit which develops an electrostatic latent image formed on the surface of the electrophotographic photosensitive member with toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning unit which cleans the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after the toner image has been transferred to a transfer material, and is detachably mountable to a main body of an electrophotographic apparatus, the surface layer of the electrophotographic photoreceptor contains a polycarbonate resin having a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structural unit represented by the following formula (3), the toner has toner particles containing a resin and an external additive, the external additive comprises particles of a silicon atom-containing compound, a content ratio of the silicon atom-containing compound particles in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to the total mass of the toner; A process cartridge comprising: [ka] [ka] [ka] (Configuration 2) A process cartridge which integrally supports an electrophotographic photosensitive member having a surface layer, a developing unit which develops an electrostatic latent image formed on the surface of the electrophotographic photosensitive member with toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning unit which cleans the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after the toner image has been transferred to a transfer material, and is detachably mountable to a main body of an electrophotographic apparatus, a total ion chromatogram (TIC) obtained by subjecting the polymer component recovered from the surface layer of the electrophotographic photoreceptor to pyrolysis gas chromatography mass spectrometry in the presence of tetramethylammonium hydroxide (TMAH) has a mass spectrum including at least components at m / z=242 and m / z=227, and a mass spectrum including at least components at m / z=296, m / z=253, m / z=145, and m / z=121; Deuterated chloroform for the polymer component 1 H-nuclear magnetic resonance spectrum has peaks at 2.35±0.02 ppm and 2.40±0.02 ppm; the toner has toner particles containing a resin and an external additive, the external additive comprises particles of a silicon atom-containing compound, a content ratio of the silicon atom-containing compound particles in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to the total mass of the toner; A process cartridge comprising: (Configuration 3) The process cartridge according to Configuration 1, wherein in the polycarbonate resin, the content ratio of the structural unit represented by the formula (2) is 40 mol % or more and 60 mol % or less with respect to the total content of the structural unit represented by the formula (2) and the content of the structural unit represented by the formula (3). (Configuration 4) The process cartridge according to configuration 1 or 3, wherein in the polycarbonate resin, the total content ratio of the structural unit represented by the formula (2) and the structural unit represented by the formula (3) is 40 mol % or more and 60 mol % or less with respect to the total content of the structural unit represented by the formula (1), the content of the structural unit represented by the formula (2), and the content of the structural unit represented by the formula (3). (Configuration 5) 5. The process cartridge according to any one of Configurations 1 to 4, wherein the particles of the silicon atom-containing compound are silica particles. (Configuration 6) 6. The process cartridge according to any one of Configurations 1 to 5, wherein the external additive contains hydrotalcite particles. (Configuration 7) 7. The process cartridge according to claim 6, wherein the hydrotalcite particles have fluorine atoms. (Configuration 8) The process cartridge according to any one of Configurations 1 to 7, wherein the contact force per unit length in the longitudinal direction of the cleaning blade against the surface of the electrophotographic photosensitive member is 0.196 N / cm or more and 0.490 N / cm or less. (Configuration 9) An electrophotographic apparatus comprising the process cartridge according to any one of configurations 1 to 8. [Explanation of symbols]
[0101] 1. Electrophotographic photoreceptor 2-axis 3. Charging means 4 Exposure light 5. Developing method 6 Transfer Method 7 Transfer material 8 Fixing Method 9 Cleaning Method 10 Pre-exposure light 11 Process cartridge 12 Guidance means
Claims
1. A process cartridge which integrally supports an electrophotographic photosensitive member having a surface layer, a developing unit which develops an electrostatic latent image formed on the surface of the electrophotographic photosensitive member with toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning unit which cleans the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after the toner image has been transferred to a transfer material, and is detachably mountable to a main body of an electrophotographic apparatus, the surface layer of the electrophotographic photoreceptor contains a polycarbonate resin having a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structural unit represented by the following formula (3), the toner has toner particles containing a resin and an external additive, the external additive comprises particles of a silicon atom-containing compound, a content ratio of the silicon atom-containing compound particles in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to a total mass of the toner, The particles of the silicon atom-containing compound are silica particles. A process cartridge comprising: 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】
2. A process cartridge which integrally supports an electrophotographic photosensitive member having a surface layer, a developing unit which develops an electrostatic latent image formed on the surface of the electrophotographic photosensitive member with toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning unit which cleans the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after the toner image has been transferred to a transfer material, and is detachably mountable to a main body of an electrophotographic apparatus, a total ion chromatogram (TIC) obtained by subjecting the polymer component recovered from the surface layer of the electrophotographic photoreceptor to pyrolysis gas chromatography mass spectrometry in the presence of tetramethylammonium hydroxide (TMAH) has a mass spectrum including at least components at m / z = 242 and m / z = 227, and a mass spectrum including at least components at m / z = 296, m / z = 253, m / z = 145, and m / z = 121; Deuterated chloroform for the polymer component 1 H-nuclear magnetic resonance spectrum has peaks at 2.35±0.02 ppm and 2.40±0.02 ppm; the toner has toner particles containing a resin and an external additive, the external additive comprises particles of a silicon atom-containing compound, a content ratio of the silicon atom-containing compound particles in the toner is 2.0% by mass or more and 3.0% by mass or less with respect to a total mass of the toner, The particles of the silicon atom-containing compound are silica particles. A process cartridge comprising:
3. 2. The process cartridge according to claim 1, wherein in the polycarbonate resin, a content ratio of the structural unit represented by the formula (2) is 40 mol % or more and 60 mol % or less with respect to a total content of the structural unit represented by the formula (2) and a content of the structural unit represented by the formula (3).
4. 2. The process cartridge according to claim 1, wherein in the polycarbonate resin, a total content ratio of the structural unit represented by the formula (2) and the structural unit represented by the formula (3) is 40 mol % or more and 60 mol % or less with respect to a total content of the structural unit represented by the formula (1), the content of the structural unit represented by the formula (2), and the content of the structural unit represented by the formula (3).
5. The process cartridge according to claim 1 , wherein the external additive contains hydrotalcite particles.
6. 6. The process cartridge according to claim 5, wherein the hydrotalcite particles contain fluorine atoms.
7. 2. The process cartridge according to claim 1, wherein a contact force per unit length in a longitudinal direction of said cleaning blade against the surface of said electrophotographic photosensitive member is 0.196 N / cm or more and 0.490 N / cm or less.
8. 8. An electrophotographic apparatus comprising the process cartridge according to claim 1.
Citation Information
Patent Citations
Image forming method, image forming apparatus and process cartridge
JP2010139985A
Image forming apparatus
JP2012083448A
Process cartridge and electrophotographic image formation device
JP2019095672A
Process cartridge and electrophotographic device
JP2019095679A
Polycarbonate copolymer, and coating liquid and electrophotographic photosensitive body using same
WO2013099965A1